2014
DOI: 10.2478/pjs-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable Elderly Survey 13 as a Screening Method for Frailty in Polish Elderly Surgical Patient - Prospective Study

Abstract: The prevalence of frailty as diagnosed by CGA was 59.4%. There was significantly higher number of frail patients in the oncological group (78% vs. 31%; p<0.01). According to the frailty screening methods, the frailty prevalence was 45.3%. The VES-13 score had a 60% sensitivity and 78% specificity in detecting frailty syndrome. The positive and negative predictive value was 81% and 57%, respectively. The overall predictive capacity was intermediate (AUC=0.69) CONCLUSIONS: At present, the VES-13 screening tool f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
(7 reference statements)
0
13
0
Order By: Relevance
“…After title, abstract, and full-text review, 18 articles 12,13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] reporting 17 studies were included from 11 380 citations (eFigure 1 in the Supplement). An abstract included in the previous review and subsequently published in a peer-reviewed journal was included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After title, abstract, and full-text review, 18 articles 12,13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] reporting 17 studies were included from 11 380 citations (eFigure 1 in the Supplement). An abstract included in the previous review and subsequently published in a peer-reviewed journal was included.…”
Section: Resultsmentioning
confidence: 99%
“…Median sample size was 108 (range, 28-1435) patients. Only 5 studies 23,24,28,36,38 reported follow-up duration (30 days-12 months). Ten studies 12,[23][24][25][26][27][28][29][30]38 included mixed cancer populations, with fewer studies reporting hematological malignant neoplasms (n = 5), [31][32][33][34][35] head and neck cancer (n = 1), 36 and prostate cancer (n = 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Vulnerable Elders Survey (VES-13) or Geriatric 8 (G8) [ 21 ], that are quick-to-administer but the gold standard is a detailed geriatric assessment which is an efficient and objective assessment tool that can identify frail older patients [ 1 ]. However, the aim of GA is not only to identify a frail individual but also to recognize the subclinical conditions (GA identify up to 40% of new age-related problems that were not detected in standard clinical management) [ 22 ], specific health needs of older patient and to design an intervention that can decrease the frailty and allow safe surgical treatment. GA in preoperative assessment is well described in general surgery, thoracic surgery, and orthopaedics [ 23 ], but not in urology.…”
Section: Resultsmentioning
confidence: 99%
“…23 Another study has estimated the CGA-oriented 'fragility' syndrome in patients aged >65, wherein 78% of the VES-13 score has been determined to demonstrate fragility syndrome. 22 Maia et al (2012) have also stated that the scale is valid and reliable as well as easy to implement. The scale with a 0.70 Cronbach's alpha value defines the vulnerable group at a better level 24 .…”
Section: Relationship Between Ves-13tr and Activities Of Daily Livingmentioning
confidence: 99%
“…There is a statistically significant relationship between VES-13Tr and ADL (p<0.001; Studies investigating whether the scale is valid and reliable have been carried out in different countries. 13,15,16,[22][23][24][25] In all these studies, a score of three has been considered as the breakpoint. In addition, the scale has been found to be highly reliable in CGA.…”
Section: Relationship Between Ves-13tr and Activities Of Daily Livingmentioning
confidence: 99%